A logic scoring of preference algorithm using ISO/IEC 25010:2011 for open source web applications Moodle and Wordpress - Africa, Aaron Don M. (Animo Repository, 2018)
An open source is software in which the source code is freely available and may be distributed or revised. The internet is composed of a variety of these systems and is frequently used. One category of open source systems is web applications. Examples of open source web applications are Moodle and Wordpress. One problem of open source web applications is because their codes are freely available and revised many times by different programmers it may not be standard and optimized. Logic scoring of preference is an evaluation methodology with theoretical foundations in fuzzy logic and optimization systems. This methodology allows the nonlinear aggregation of a large number of input criteria without the loss of important data. This research will develop a novel logic scoring of preference algorithm that evaluates open source web applications Moodle and Wordpress to follow the International standard ISO/IEC 25010:2011. A new metric for open source web application quality will be presented and will be focused on the usability and functional suitability of the system. This will serve as a guide for the developers of these programs to further improve the software and optimizing it. © 2006-2018 Asian Research Publishing Network (ARPN).